Bacterial pneumonia score to identify bacterial pneumonia - Ied Imilda; Finny Fitry Yani; Didik Hariyanto; Darfioes Basir (Paediatrica Indonesiana, 2015)
Background Pneumonia is caused by either bacterial or viraletiologies, with similar symptoms in children. The bacterialpneumonia score (BPS) is a clinical assessment comprised ofseveral investigations: age, assessment of axillary temperature,absolute neutrophil count, band neutrophil percentage, andinterpretation of radiological examination. The score will use todifferentiate the etiology of pneumonia.Objective To determine the sensitivity, specificity, positivepredictive value, and negative predictive value of BPS inidentifying bacterial pneumonia in children.Methods This diagnostic study was performed at Dr. M. DjamilHospital, Padang, West Sumatera where subjects were selected byconsecutive sampling. Fifty-seven patients were diagnosed withpneumonia. Three patients suffered from ventricular septal defects,8 patients refused to provide blood specimens and 3 patients’chest X-rays could not be interpreted, hence, 43 subjects wereincluded in the study. Chest X-rays were interpreted by a pediatricpulmonology consultant. Leukocyte and differential counts wereperformed by a clinical pathology consultant. Subjects’ BPS scoreswere compared to multiplex PCR examinations of blood specimens,as the gold standard.Result Of 43 subjects, 27 (62.79%) were male. Subjects’ mean age was 29.3 (SD 21.5) months. Twenty (46.51%) subjects had good nutritional status, 4 (9.31%) subjects had axillary temperature ≥39°C, and 22 (51.16%) subjects had absolute neutrophil counts ≥8.000/mm3. Bacterial pneumonia score (BPS) had 69% sensitivity, 60% specificity, 42% positive predictive value, and 81% negative predictive value.Conclusion In this study, BPS has low sensitivity and specificityfor identifying bacterial pneumonia.